Hopo: The dread that clings - Rangiwai, Byron (Te Kaharoa, 2021)
Hopo is a term that has many definitions and explanations. This is complicated further by the fact that te reo Māori does not translate directly into English. There is very little literature concerning hopo. What does exist mainly explains hopo in spiritual terms. At the same time, hopo is mentioned very briefly in psychological terms. Supported by the extant literature, this paper will briefly explain hopo and recommend future research.